Digital Trends in Strategic Development of Nuclear Power Engineering Enterprises - Golovko, Maria V; Setrakov, Alexander N; Volgina, Svetlana V; Tkachev, Vladimir G (Глобальная ядерная безопасность, 2023)
This article substantiates the benefits of digitalization for the strategic development of industrial enterprises. The main directions of digital transformation of all business processes are defined. The experience and key results of the technological development strategy of the mechanical engineering division of SC "Rosatom" and the specifics of the nuclear power industry as a management object are considered and presented.